A review of the woody bamboos (Poaceae: Bambusoideae: Bambuseae) of Trinidad and Tobago - Christopher D. Tyrrell; J. Francisco Morales (Advances in Bamboo Science, 2024)
Trinidad and Tobago are important islands to Neotropical woody bamboo taxonomy. Trinidad is a type locality for two widely applied names with poorly defined species concepts: Arthrostylidium pubescens and A. excelsum, and two potentially endemic species: Chusquea cylindrica and Rhipidocladum prestoei. Few resources exist for the islands to adequately identify all the woody bamboo species that putatively grow there. The serialized vascular flora of Trinidad and Tobago (1928–1992), for instance, lacks a treatment for Poaceae. Moreover, the most speciose native genus, Arthrostylidium, is only partially revised, with the emphasis on the South American species and not those of the West Indies. Our objective is to critically review the woody bamboos of Trinidad and Tobago, clarify which species are or have been known from the islands, and provide an identification key, species accounts and distribution maps for the revised list of taxa. We conducted fieldwork campaigns in 2021–2023, and reviewed herbarium specimens and human observation records of woody bamboos from the islands. Newly collected specimens were vouchered and all woody bamboo records were georeferenced and plotted using QGIS. We confirmed two species of native woody bamboo and four species of introduced woody bamboo were extant on Trinidad. An additional three Western Hemisphere species have historic records of occurrence on the islands. Native species diversity correlated well with previously identified floristic hotspots. One introduced species, Bambusa vulgaris, is common on both islands. To the best of our knowledge, there are currently no native woody bamboo species present on Tobago, however, A. pubescens appears to have been growing along the Main Ridge in the past. The historic presence of some species not currently found may be the result of dynamic and/or stochastic colonization events among the islands and mainland South America.